The impact of renal function on the incidence and prognosis of new-onset atrial fibrillation in acute myocardial infarction. (25th November 2020) - Cosentino, N; Campodonico, J; Ballarotto, M; Milazzo, V; Moltrasio, M; De Metrio, M; Lucci, C; Rubino, M; Marana, I; Assanelli, E; Grazi, M; Lauri, G; et al.
Abstract: Introduction: Atrial fibrillation (AF) is a frequent complication of acute myocardial infarction (AMI) and is associated with a worse prognosis. Patients with chronic kidney disease are more likely to develop AF. Whether the association between AF and renal function is also true in AMI has never been investigated. Purpose: The aim of the study was to assess the incidence of new-onset AF according to renal function, estimated at hospital admission, and its relationship with short-term outcome and long-term all-cause mortality in a large real-world cohort of AMI patients. Methods: We prospectively enrolled 2, 445 AMI patients. New-onset AF was recorded during hospitalization. Glomerular filtration rate (eGFR) was estimated at admission and patients were grouped according to their renal function (group 1 [n=1, 887]: eGFR>60; group 2 [n=492]: eGFR 60–30; group 3 [n=66]: eGFR<30 ml/min/1.73m 2 ). The primary endpoint was AF incidence. In-hospital and long-term (median 5 years) all-cause mortality were the secondary endpoints. Results: The AF incidence in the whole population was 10% and it was associated with a higher in-hospital (5% vs. 1%; P<0.0001) and long-term mortality (34% vs. 13%; P<0.0001). The AF incidence was 8%, 16%, 24% in groups 1, 2, 3, respectively (P<0.0001). In each group, in-hospital mortality was higher in AF patients (3.5% vs. 0.5%, 6.5% vs. 3.0%, 19% vs. 8%, respectively; P<0.0001). A similar trend was observed for long-term mortality (20% vs. 9%, 51% vs. 24%, 81% vs. 50%, respectively; P<0.0001). The higher risk for in-hospital and long-term mortality associated with AF in each group was confirmed also after adjustment for major confounders. Conclusions: The study demonstrates that the incidence of new-onset AF during AMI, as well as its associated in-hospital and long-term mortality, increases in parallel with the severity of renal dysfunction assessed at hospital admission. Funding Acknowledgement: Type of funding source: Private hospital(s). Main funding source(s): Centro Cardiologico Monzino, IRCCS, Milan, Italy